Segurança e qualidade do transporte público coletivo urbano de São Carlos sob a perspectiva das mulheres - Jacobino, Ornela Maria Alves (2023)
Women are the majority of the population in both Brazil and São Carlos, however they continue to face limited representation across various domains, which contributes to the lack of the sense of security and support in the city. Public transportation harbors the potential to provide self-sufficiency among women through employment opportunities, facilitating their access to healthcare, and education. Achieving equitable access to public transport involves understanding how it accommodates the efficiency, sustainable mobility, and security needs of both genders. The main goal of this study is to examine urban public transportation in São Carlos through the users’ perspective, focusing on quality and security, to conduct a gender-based analysis of the results from women’s point of view. The study was derived from the data generated by an online survey with multiple choice questions related to User Profile and Quality and Security of Public Transportation, based on the UITP-CittaMobi National Survey on Public Transportation Safety (UITP-CITTAMOBI, 2018) and the global quality assessment matrix model for users presented by Ferraz and Torres in 2004. The analysis of the results revealed that the perception of the system quality remains a relatively consistent pattern across genders. However, concerning security, women’s and men's perspectives significantly contrast on specific aspects. Therefore, it is relevant to analyze the quality and security of public transport through a gender-oriented lens. This approach aims to build a more equitable and sustainable society promoting parity in urban mobility through a targeted approach to the implementation of improvements.